2001
DOI: 10.1097/00003246-200106000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Can generic scores (Pediatric Risk of Mortality and Pediatric Index of Mortality) replace specific scores in predicting the outcome of presumed meningococcal septic shock in children?

Abstract: The PRISM score performed better than the PIM score, and was not surpassed by specific scores. Thus, we propose its use for outcome prediction in children with septic shock and purpura. However, if the PRISM score is to be used as inclusion criterion for clinical trials, it should be evaluated within a few hours after admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
3
24
1
8
Order By: Relevance
“…Os autores apontam como uma vantagem do PIM em relação ao PRISM o fato de o PIM ser baseado em apenas oito variáveis, todas coletadas no momento da internação, o que facilitaria a coleta dos dados e evitaria o efeito no resultado do escore após 24 horas de diferentes estratégias de manejo intensivo 14 . Diversos artigos que avaliaram o PIM mostraram que ele apresenta um bom desempenho para predizer morte [11][12][13][14][15][16] . Em 2003, o PIM Study Group publica uma versão revisada do PIM, o PIM-2 16,17 , que, comparada à versão original 18 , seria mais bem calibrada, mais segura e com melhor ajuste em diferentes grupos diagnósticos.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Os autores apontam como uma vantagem do PIM em relação ao PRISM o fato de o PIM ser baseado em apenas oito variáveis, todas coletadas no momento da internação, o que facilitaria a coleta dos dados e evitaria o efeito no resultado do escore após 24 horas de diferentes estratégias de manejo intensivo 14 . Diversos artigos que avaliaram o PIM mostraram que ele apresenta um bom desempenho para predizer morte [11][12][13][14][15][16] . Em 2003, o PIM Study Group publica uma versão revisada do PIM, o PIM-2 16,17 , que, comparada à versão original 18 , seria mais bem calibrada, mais segura e com melhor ajuste em diferentes grupos diagnósticos.…”
Section: Introductionunclassified
“…Diversos artigos que avaliaram o PIM mostraram que ele apresenta um bom desempenho para predizer morte [11][12][13][14][15][16] . Em 2003, o PIM Study Group publica uma versão revisada do PIM, o PIM-2 16,17 , que, comparada à versão original 18 , seria mais bem calibrada, mais segura e com melhor ajuste em diferentes grupos diagnósticos. Essa nova versão ainda não foi avaliada de forma independente, carecendo de maiores informações quanto a sua performance em outras regiões e, por ter sido publicada após o início deste estudo, não está incluída neste trabalho.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…14 Several articles that have evaluated the PIM have shown that is performs well at predicting death. [11][12][13][14][15][16] In 2003 the PIM Study Group published a revised version of the PIM, the PIM-2 16,17 which, compared with the original version, 18 is supposed to be better calibrated, safer and better adjusted for varying diagnostic groups. This new version has not yet been evaluated independently and more information is necessary with respect of its performance in other regions and, because it was published after this study began, it was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, those studies that have been performed independently have not used heterogenic groups of patients from PICUs, but have investigated certain specific disease categories, 11,16,21 new versions of the methods 10 or homogenous groups of high mortality patients. 22 No studies of this type have been published in Latin America.…”
Section: Introductionmentioning
confidence: 99%